Proud of you, so act for you? The role of national pride in promoting individual pro-environmental tendencies - Wang, Pengcheng; Dong, Zhiqiang; Cai, Shenggang; Xiao, Min (Frontiers in Environmental Science, 2023)
The promotion of pro-environment behaviors is important for achieving national and global environmental protection goals. We investigate the factors that promote the translation of national environmental will into individuals’ pro-environmental tendencies (PET) from the perspective of national pride. A large-scale survey and two experiments in the Chinese context were conducted to investigate the relationship between national pride and PET and the tools for promoting national pride and PET. The results show that national pride is positively associated with individuals’ PET. Priming with national achievements promotes individuals’ PET by inspiring their national pride. Both political-economic achievements and historical-cultural achievements can inspire Chinese people’s national pride, but political-economic achievements are more effective for Chinese people. And priming national pride combined with highlighting national environmental norm information could more effectively increase PET. Our findings illuminate the role of individuals’ national pride in influencing their PET, suggesting a potential means for nudging individuals’ pro-environmental actions.